The Strengths and Weaknesses of Extensive Reading using Wattpad; Students’ Perceptions - Intan Permatasari; Agus Wijayanto; Diah Kristina (Indonesian Journal of EFL and Linguistics, 2020)
This study aims to explore the strengths and weaknesses of extensive reading using Wattpad platform based on students’ perceptions. Extensive reading allows students to have more variation in their reading materials as they can read authentic texts from various sources that it is actually applied outside the class room for most people consider it as joyful reading. The advancement of technology over the times enables people to do many activities online, including extensive reading activity. Hence, Wattpad is believed to provide enormous free and paid reading materials that can support extensive reading for the students. To achieve the objectives, this study is in the form of case study. The data were collected through in-depth interview with the participants. The participants were two undergraduate students majoring English Education from two different universities in Indonesia. The participants were selected purposively because they were known to have been doing extensive reading activity on Wattpad for a quite long time, specifically for five years. The research findings showed several strengths of using Wattpad for extensive reading such as Wattpad gives students numerous and various sources of reading materials; extensive reading on Wattpad is a fun and enjoyable experience; extensive reading on Wattpad is more practical than using printed-books; extensive reading on Wattpad is money-saving; the reading materials on Wattpad have good quality contents; extensive reading through Wattpad improves students English’s skills unconsciously as well as the reading habit. Meanwhile, there are several weaknesses of extensive reading using Wattpad according to students such as; similarities in the reading materials sometimes make them boring to read; using the platform for a certain long time can potentially cause tired eyes; there are other distractions that can disrupt the extensive reading activity.